2016
DOI: 10.1051/epjconf/201611705001
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear physics and particle therapy

Abstract: The use of charged particles and nuclei in cancer therapy is one of the most successful cases of application of nuclear physics to medicine. The physical advantages in terms of precision and selectivity, combined with the biological properties of densely ionizing radiation, make charged particle approach an elective choice in a number of cases. Hadron therapy is in continuous development and nuclear physicists can give important contributions to this discipline. In this work some of the relevant aspects in nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This results in the production of a range of nuclear fragments at the target site, including short-range, high-LET charged particles, and a mixture of fast and thermal neutrons. Due to scattering within the target tissue, the thermal neutrons are emitted nearly isotropically from the point of collision, and they deposit their energy in the region surrounding the path of the incident ion beam via a succession of elastic and inelastic collisions 10 , 11 . The thermal neutrons irradiate both target and non-target tissues indiscriminately, and they deposit a fraction of the beam’s kinetic energy outside of the target volume 9 .…”
Section: Introductionmentioning
confidence: 99%
“…This results in the production of a range of nuclear fragments at the target site, including short-range, high-LET charged particles, and a mixture of fast and thermal neutrons. Due to scattering within the target tissue, the thermal neutrons are emitted nearly isotropically from the point of collision, and they deposit their energy in the region surrounding the path of the incident ion beam via a succession of elastic and inelastic collisions 10 , 11 . The thermal neutrons irradiate both target and non-target tissues indiscriminately, and they deposit a fraction of the beam’s kinetic energy outside of the target volume 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In 1946, Robert R. Wilson was the first to propose the use of proton beams for the treatment of cancer 11 . The major advantage of this technique is its depth‐dose profile characterized by a significant increase in the dose deposited at the end of the particle path 12 . Based on clinical data and in vivo experiments, Paganetti et al have demonstrated that the relative biological effectiveness (RBE) of protons was close to 1.1.…”
Section: History Of Radiation In Cancermentioning
confidence: 99%